Menjadi Manusia Partisipan di Tengah Pandemi : Sebuah Tinjauan Antropologis-Filosofis Gabriel Marcel Tentang Manusia Partisipan Sebagai Jawaban atas Dunia yang Sakit - Kardianus Manfour (Parahyangan Catholic University, 2021)
This paper specifically explores the human understanding of participant Gabriel Marcel, which is motivated by the problems surrounding the COVID-19 pandemic. Participant human understanding is a form of answer to the problem of human existence in the midst of a sick world. The methodology of this paper is interpretive. The author tries to elaborate Gabriel Marcel's thoughts with the phenomena surrounding the pandemic and also the new world order due to the pandemic. From the results of this elaboration, the author finds that in order to reorganize this ailing world, everyone must be a human participant and not a human spectator. The journey to become a participant human begins with an awareness of his existence as a human being. The concept of human participant Gabriel Marcel must be recognized as a sharp philosophical reflection in understanding human existence. This thought is the starting point for the birth of humans who are aware of their social responsibilities as human participants who always have a heart towards others and the world.